Waste Plastic Pyrolysis Industry: Current Status and Prospects - Donghae Kim; Myeonghun Han; Nahyun Kim; Jihyeon Kim; Sokhee P. Jung (대한환경공학회지, 2024)
Pyrolysis is a technology that can produce pyrolysis oil by decomposing waste plastic, and has the advantage of being able to process contaminated waste plastic that is impossible to process with other technologies. In Korea, where the amount of waste plastic is increasing and natural resources such as fossil fuels are lacking, pyrolysis technology is attracting attention under the keyword ‘urban oil field’. The Ministry of Environment of the Republic of Korea announced a ‘plan to revitalize waste plastic pyrolysis’ to increase the proportion of waste plastic pyrolysis treatment from 0.1% in 2021 to 10% in 2030. The products of pyrolysis are both fuel and plastic raw materials, but the processing consumes significant energy. Therefore, as criticism continues that the marketability and economic feasibility of pyrolysis technology is poor, questions are being raised about its environmental friendliness. Against this background, this study investigated international trends in pyrolysis technology and performed a detailed comparative analysis with other technologies from an environmental perspective. According to the results of this study, currently environmentally advanced countries are very negative about using pyrolysis oil as fuel, and the following policy directions are suggested. 1) In order to comply with the mandatory use ratio of plastic recycled raw materials and at the same time achieve eco-friendliness, it is recommended to use pyrolysis technology as a plastic recycled raw material production technology rather than fuel conversion. 2) Since pyrolysis emits more greenhouse gases than physical recycling, pyrolysis technology is used as a complementary method to physical recycling to process waste plastics that are difficult to physically recycle. 3) Since physical recycling is very important in the resource circulation of waste plastic, the development of separation and sorting technology is promoted nationally.